Earth Sciences in India, Problems and Opportunities with Special Reference to Developmental Programmes - Murthy, M. V. N. (Journal of Information and Knowledge, 1978)
India has a fairly long history of systematic geological survey activities. Since independence such activities have been diversified and a number of new agencies setup. Even then, there are certain gaps in our information regarding certain areas. The vast Indo-Gangetic alluvial plains, the difficult Himalayan terrain and the extensive off-shore areas have been neglected so far. The use of remote sensing techniques, including the use of imagery and active systems and the use of computer for better analysis of data have become necessary. Another major gap in our information is regarding the chemistry of soils, ores, etc. There is also need for modem surveys in respect of glaciology which is vital to understanding the Himalayan river system. Major areas of intensive collaborative research studies are experimental petrology End rock deformation and also palaeobiology.